The true costs of loss and damage in the agrifood sector: What's next? CGIAR Issue Brief Series for Informing COP 29 | Number 2 - Mukherji, Aditi; Castro, A.; Bowa, E.; Chilambe, P.; Deepa, J.; Kumar, S.; Majdalani, R.; Marshall, Suzie; Ringler, Claudia (CGIAR Climate Change Impact Platform, 2024)
Agriculture is most impacted by climate change induced losses and damages as it is one of the most weather exposed sectors, with many vulnerable people dependent on this sector for their livelihoods. About one-third (or 35 percent) of current climate action plans explicitly refer to loss and damage, highlighting the urgency of the issue, especially among countries with agriculture as a priority. The Loss and Damage fund, as and when operationalized, should prioritize sectoral allocations to agriculture, and particularly smallholders to protect food security and livelihoods of the most vulnerable. Such finance must be new, additional and grant based.